Integration of paper microfluidic sensors into contact lenses for tear fluid analysis. Issue 21 (18th September 2020) - Moreddu, Rosalia; Elsherif, Mohamed; Adams, Hadie; Moschou, Despina; Cordeiro, Maria F.; Wolffsohn, James S.; Vigolo, Daniele; Butt, Haider; Cooper, Jonathan M.; Yetisen, Ali K.
Abstract : Paper microfluidic sensors were integrated into laser-inscribed contact lenses to provide an in situ platform for tear analysis with smartphone readouts. Abstract : In this article, using the integration of paper microfluidics within laser-inscribed commercial contact lenses, we demonstrate the multiplexed detection of clinically relevant analytes including hydrogen ions, proteins, glucose, nitrites and l -ascorbic acid, all sampled directly from model tears. In vitro measurements involved the optimization of colorimetric assays, with readouts collected, stored and analyzed using a bespoke Tears Diagnostics smartphone application prototype. We demonstrate the potential of the device to perform discrete measurements either for medical diagnosis or disease screening in the clinic or at the point-of-care (PoC), with future applications including monitoring of ocular infections, uveitis, diabetes, keratopathies and assessing oxidative stress.